PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 009 TELUK NILAP KECAMATAN KUBU - Antosa, Zariul Antosa Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : This research is motivated lowIPA students learning outcomes ClassIV 009 Bay State Primary School Nilap. While the purpose of this research is toimprove the learning outcomes of the fourth grade science students 009 Bay StatePrimary School Nilap to implement guided inquiry learning model. The resultsshowed an increase in activity of the teacher, in which the first cycle of the firstmeeting of the percentage of the activity obtained with 60% of teachers and 65%second meeting with enough categories. The percentage of all teachers in thesecond cycle was 75% dipertemuan first, second meeting increased to 95% withvery good category. Increased activity of students, meeting Ipada first cyclepercentage is 55% less category, while the second meeting in the first cycle was70% category enough. On data from observations of student learning activities inthe second cycle of meeting the ever increasing I and II. At the first meeting of thestudent activity is 80% good category, while the second meeting of the studentactivity 95% excellent. Increase in the average science student learning outcomes,basic score value averages the fourth grade students learn science Gulf NilapSDN 009 is increased to 72.08 to 58.31 daily test cycle I value with an increase of23.61%. While on the basis of the score to the second cycle again increased, withan increase of 38.86%. The average value of daily test students in the secondcycle was 80.97. This increase indicates that the application of inquiry learningmodel is very effective in improving learning outcomes IPA 009 fourth gradestudents of SDN Gulf Nilap Kubu distric.Keywords : Model of inquiry learning, science learning outcomes